Smartphone Use, Technology Affordance for Healthcare and Elders' Life Satisfaction - Li, Geling; Jin, Chenfei; Zhao, Bin; Wu, Bao (Frontiers in Public Health, 2022)
Previous studies have examined how smartphones influence the life satisfaction of the elderly, but the existence of conflicting conclusions suggests the existence of a “black box”. In this study, using a survey from 941 elders, we examine whether smartphone use can improve life satisfaction of the elders by inducing emotional affordance offered by social networking Apps and functional affordance offered by healthcare system Apps. It is found that both emotional affordance and functional affordance acted as intermediating variables between the use of smartphone and elders' life satisfaction. In addition, it is founded that living arrangement with adult children moderates the positive impact of smartphone use on functional affordance, but there was no such moderating effect on emotional affordance. This study offers insights about how digital healthcare innovation will be applied to increase well-being of elders by applying framework of selective optimization with compensation.